A Cognitive Domain Analysis of English Stance Adverbs - fatah, Azad hasan; Hassan, Shanaw Rashad (Sulaimani Journal for Humanities, 2025)
This paper adopts the domain theory of meaning to explain stance adverbs in English. Stance refers to the viewpoint taken by a speaker vis-à-vis an event or a situation. In English, there are adverbs which express stance. In everyday communication, language users may face difficulties in using these adverbs without considering their proper use in contexts. Thus, the study aims to find out the precise meanings of these adverbs. In Cognitive Linguistics, stance adverbs are grouped in different domains representing different facets where they converge and diverge. For instance, although the two stance adverbs politely and tactfully evoke the domain of attitude and occupies the same facet, each has a different meaning. Politely shows correct behavior in accordance with social norms of society. Whereas, tactfully means showing tact in a specific situation to avoid upsetting someone. The main conclusion of the study is that stance adverbs have subtle differences in meaning by grouping them under different domains and each stan
Keywords: Cognitive Linguistics; Cognitive Grammar; stance adverbs; domain theory and facet